The Profile of Leprosy Patients in Aceh: Retrospective Study - Nanda Earlia; Sulamsih Sri Budini; Dea Silvia Ramadana; Mikyal Bulqiah; Aqil Yuliawan Tasrif; Randika Richard R; Muhammad Adji Pangestu; Annisa Raihani; Auni Batrisyia; Eva Cahyaningsih; Fanny Adlin Nurafika; Istiqomah Genepo; Nadira Sabrina Mufti (Faculty of Medicine, Universitas Airlangga, 2022)
Backgrounds: Morbus Hansen or leprosy is a chronic granulomatous infectious disease caused by the obligate intracellular Mycobacterium leprae bacillus. Leprosy can cause loss of sensation in the skin with or without lesions and body dysfunction during the course of the disease. In Aceh, there were 337 new cases of leprosy in 2019 and this was the highest case in Sumatra. Purpose: To analyze the profile of leprosy patients in the Department of Dermatology and Venereology of RSUDZA Banda Aceh. Methods: Observational descriptive study with retrospective design, using medical record of leprosy patients who visited Dermatology and Venereology Outpatient Clinic RSUDZA Banda Aceh for the period of January 2017 – December 2021. Result: A total of 183 leprosy patients were obtained from the study. Most cases occured in male patients (68.3%), the majority was in the 18-40 year age group (60.1%), most patients live outside of Banda Aceh (71%). The most frequently reported type of leprosy was the multibacillary type (71.6%). Leprosy patients without disability were 35.5%, the majority did not experience a leprosy reaction (71%), the most common morphology of the lesion was erythematous (29.5%), and the highest proportion of the bacteriological and morphological index was negative (46.4% and 50.8% respectively). Conclusion: The diagnosis of leprosy was based on clinical, bacteriological, and histopathological features. Early diagnosis, patient access to treatment, early initiation of treatment and adherence to therapy would reduce the disease transmission thus would decrease the prevalence of leprosy in Aceh.